Develop A Prototype of An Unmanned Water Surface Garbage Cleaning Robot Using Photovoltaic Panel - Muhamad Kamal, Aiman Fatina; Yahaya, Jabbar Al-Fattah (Evolution in Electrical and Electronic Engineering, 2023)
The Water Surface Garbage Cleaning Robot (WSGCR) project addresses the problem of water pollution caused by waste accumulation in rivers and other water bodies. Current approaches to cleaning water surfaces often require significant resources and manual labor. Therefore, this project aims to propose an effective solution by developing a WSGCR that can collect waste and increase operational hours through the integration of a photovoltaic (PV) system. The project’s objectives encompass the design and development of a small-scale prototype WSGCR and the implementation of the PV system to extend its operation. By leveraging renewable energy sources such as solar power, the WSGCR offers a sustainable and efficient alternative to traditional cleaning methods. Extensive testing and experimentation are conducted to ensure the robot’s performance and efficiency, utilizing the Blynk application as an IoT platform for remote control. The WSGCR incorporates a conveyor system for waste collection and motor drivers for precise movement control. The integration of PV panel technology for battery charging is tested and compared to conventional methods. It is found that the PV panel charge rate for an hour is 2.4% rather than using a conventional method which is 3.9%. Also found that by integrating the PV panel the operation of WSGCR for one and a half hours has a decrement of 0.8% rather than using only battery which is 5.47%. The Integrated PV panel has increased operation hours by 4.67% in one and a half hours. Real-time feedback on the robot’s functionality is provided through sound indicators using a buzzer in the Blynk interface. The successful realization of this project will contribute to improving water quality, reducing pollution-related health risks, and conserving aquatic ecosystems.